TNFSF15 Inhibits Blood Retinal Barrier Breakdown Induced by Diabetes - Jiang, Feng (Int J Mol Sci, 2016)
Tumor necrosis factor superfamily 15 (TNFSF15) is an endogenous neovascularization inhibitor and an important negative regulator of vascular homeostasis. This study aimed to explore the potential role of TNFSF15 in diabetic retinopathy. Vitreous TNFSF15 and VEGF levels in proliferative diabetic retinopathy (PDR) patients were detected by ELISA. Retinal expression of TNFSF15 and the content of tight junction proteins (TJPs) in rats were detected by immunohistochemistry and Western blot, respectively. The blood retinal barrier (BRB) permeability was evaluated using Evans Blue (EB) dye. The TNFSF15/VEGF ratio was decreased in the vitreous fluid of patients with PDR relative to the controls, even though the expression levels of TNFSF15 were higher. TNFSF15 was dramatically decreased one month later after diabetes induction (p < 0.001), and then increased three months later and thereafter. TNFSF15 treatment significantly protected the BRB in the diabetic animals. Diabetes decreased TJPs levels in the retina, and these changes were inhibited by TNFSF15 treatment. Moreover, TNFSF15 decreased activation of VEGF both in mRNA and protein levels caused by diabetes. These results indicate that TNFSF15 is an important inhibitor in the progression of DR and suggest that the regulation of TNFSF15 shows promise for the development of diabetic retinopathy treatment strategies.